Which styles of moral reasoning predict apprehension toward consensual non-monogamy?. (October 2022) - Cunningham, Niegel C.; Mitchell, Ravyn C.; Mogilski, Justin K.
Abstract: Consensual non-monogamy (CNM) refers to any intimate relationship where partners agree to form multiple, concurrent intimate relationships. Stigma against CNM is well-documented, but its antecedents are unclear. Here, we test how apprehension toward CNM is related to moral reasoning. In Study 1, participants ( N  = 229) identified reasons why people disapprove of CNM from which we created the CNM Apprehension Scale (CNMapp ). In Study 2, participants ( N  = 726) completed the CNMapp alongside established measures of moral decision-making: the moral foundations questionnaire, the social dominance orientation scale, the zero-sum thinking in romantic relationships scale, the moral approbation scale, and the HEXACO-60. We identified five reasons for CNM apprehension: 1) anticipated relationship conflict, 2) moral belief violation, 3) reputational damage, 4) sexual health risk, and 5) same-sex intimacy. People who scored higher on CNMapp reported more zero-sum thinking about their romantic relationships, stronger purity and antiegalitarian beliefs, lower openness to experience, and greater desire for moral approbation from others. We argue that CNM apprehension can be traced to two primary concerns: unrestricted sociosexuality and risk of interpersonal conflict. We conclude by considering how moral intuitions about CNM may be adaptively mismatched to environments where technology addresses the recurrent adaptive challenges of non-monogamy. Highlights: Created and validated a measure of apprehension toward CNM (CNMapp ) Identified five categories of reasons for CNMapp Zero-sum thinking, binding foundations, and antiegalitarianism predicted CNMapp People with non-binary gender reported less CNMapp than cisgender people.